IMPROVING THE EFFICIENCYOF NATIONAL STUDENT COMPETITION - Valeriy I. Koshkin; Alexander I. Gordeev; Andrey V. Belotserkovsky; Ivan A. Kaplunov; Anna A. Maltseva; Evgeniya L. Pustovalova (Moscow Polytechnic University, 2016)
The article considers the new ways and methods for improving the efficiency of national student contests and Olympiads as a tool for identifying and supporting young talents. The authors suggest a new approach to the organization of the Olympiad movement including such principles as the limitation of the state's role (it should be only a general initiator and supporter), segmentation of contest types, determination of contestants' level, finding the optimal combinationbetween of the system's stability and its capability to develop.